Perkembangan Behavioral Accounting Wujud Open Ended Ilmu Akuntansi sebagai Sosok Social Science - Nor Hadi; Ernawati Budi Astuti (Universitas Wahid Hasyim, 2006)
The shift of accountancy dicipline has been clearly marked over the past two decades. Normative accountancy that has triumphed for a few decades and has been an icon in accounting practices has gained criticism from many parties, both practitioners and academics. It wa due tothe fact that normative accountancy which is based on researches cannotbe implemented in every day lives. Concequently, a new insight is offering a new understanding of descriptive accountancy in real life.The shift of behaviour accounting is closely related to its epistemology underpinnings, where accounting is not a mono method in nature, but it is actually multi method. That is, whitin its epistemology design, which is the way dicipline is designed,accounting is recognizingand embracing many paradigms.Therefore, accounting is an open ended dicipline that is openended in nature toward social science theories, such as sociology, anthropology and psychology,especially when it is the non positivistic epistemology that is being used as its cornerstone in accounting development researches. This is where normative accounting emerged and developed to explain the phenomenon naturally.The area of behaviral accounting development into: (1) The antecedents and consequences of using acoounting information to evaluate subordinate performance; (2) The role of budget participation in organization control; (3) The consequences of incentive compensation contrancting; (4) The antecedents and consequences of effective control and budgetting system design.